(untitled) (Eurasian Research Bulletin, 2023)
In the context of work on the draft of a new edition of the Civil Code of the Republic of Uzbekistan, the relevance and scientific novelty of the legal regulation of the method as an object of invention are determined. The role and significance of the method of invention is argued. The method is considered as an object of invention, which may give rise to certain exclusive rights. Various grounds for recognition and legal protection of the method of invention are analyzed. Considered are not only the essence of the method of invention, but also the features of the method of invention for patentability. The conclusion is formulated about the definition of the invention method, the process of performing interrelated actions on a material object using material means. And also, to characterize the methods, such signs as the presence of an action or a set of actions are used; the order in which such actions are performed in time (successively, simultaneously, in various combinations, etc.). Proposals are formulated regarding the method as an object of invention, on the improvement of civil legislation in the field of intellectual property